THE LAW ON IMPROVING THE FINANCIAL SITUATION OF THE LAY CLERGY IN THE KINGDOM OF ROMANIA - PRELIMINARIES - Vasile-Lucian GOLDAN (Management Intercultural, 2020)

(untitled)
Ensuring a constant minimum income for all clergy is an old problem of the Romanian Orthodox Church. During the royalty, the financial motivation of the lay clergy in Romania was the main concern of the synods, which tried to find support in the Parliament, forming a law project in this regard - one of the initiators being Metropolitan Iosif Naniescu. The precarious financial situation and the dissatisfaction of the lay clergy led the synods to look for new solutions to solve this problem. The chosen solutions would satisfy and displease the lay clergy, the aspirants in theology and the non-clerical staff of the parishes. Among the chosen solutions were the reduction of the number of ordinations and the monopolization of the manufacture and sale of cult candles by creating a production and a distribution network, the resulting profit following to be used to support the salaries of clerical and non- clerical staff of the churches.